2021
DOI: 10.1101/2021.06.27.450109
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Carbohydrate sulfation as a mechanism for fine-tuning Siglec ligands

Abstract: The immunomodulatory family of Siglecs recognize sialic acid-containing glycans as self, which is exploited in cancer for immune-evasion. The biochemical nature of Siglec ligands remains incompletely understood with emerging evidence suggesting the importance of carbohydrate sulfation. Here, we investigate how specific sulfate modifications affect Siglec ligands by overexpressing eight carbohydrate sulfotransferases (CHSTs) in five cell lines. Overexpression of three CHSTs (CHST1, CHST2, or CHST4) significantl… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
13
1
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 13 publications
(21 citation statements)
references
References 65 publications
2
13
1
1
Order By: Relevance
“…Notably, Siglec-9-binding to a cultured cell line was markedly enhanced by overexpression of human GlcNAc6ST2/CHST4 and GlcNAc6ST1/CHST2 [60], while the current results show a complementary action of GlcNAc6ST2 and GlcNAc6ST3 in mesothelial CL40 glycan. A previous study identified CHST4 as a mesothelium-enriched gene [61], which strongly supports the involvement of GlcNAc6ST2 in the synthesis of the CL40 epitope in the mesothelium.…”
Section: Glcnac6st2 and Glcnac6st3 Are Required For The Synthesis Of ...contrasting
confidence: 49%
“…Notably, Siglec-9-binding to a cultured cell line was markedly enhanced by overexpression of human GlcNAc6ST2/CHST4 and GlcNAc6ST1/CHST2 [60], while the current results show a complementary action of GlcNAc6ST2 and GlcNAc6ST3 in mesothelial CL40 glycan. A previous study identified CHST4 as a mesothelium-enriched gene [61], which strongly supports the involvement of GlcNAc6ST2 in the synthesis of the CL40 epitope in the mesothelium.…”
Section: Glcnac6st2 and Glcnac6st3 Are Required For The Synthesis Of ...contrasting
confidence: 49%
“…Strong masking of Siglec-7 was confirmed through greatly enhanced binding of Sig-7L liposome binding to cells treated with neuraminidase to remove cis ligands (Figure S17A). U937 cells lacking sialic acid, through an introduced mutation in cytidine monophospho-N-acetylneuraminic acid synthetase (CMAS), 49,68 also displayed significantly increased Sig7-L liposome binding compared to WT cells (Figure 5d). We deleted Siglec-7 in the CMAS −/− cells and then virally transduced them with empty lentiviral control or WT Siglec-7 (Figure S17B).…”
Section: Acsmentioning
confidence: 99%
“…31 Genetic engineering of cells has indicated that sulfation can regulate Siglec binding; however, the precise molecular mechanisms of this regulation are not well understood. 32,33 Histological studies have shown that airway tissues express high-molecular-weight ligands for Siglec-8 and 9. 34 Treatment of these tissues with keratanase-I abolished the binding of recombinant Siglec-8.…”
Section: ■ Results and Discussionmentioning
confidence: 99%